Narcissism and observed communication in couples. (15th January 2017) - Lamkin, Joanna; Lavner, Justin A.; Shaffer, Anne
Abstract: Narcissism is associated with dysfunction in interpersonal relationships. Empirically, limited information is available about how narcissism affects observed interactions in romantic relationships. In this study, we employed dyadic data analyses to investigate the effects of narcissism on relationship functioning. Young adult couples ( N  = 54 couples) participated in a neutral discussion task, and their communication behaviors (hostility, anger, and positive affect) were coded by observers. We also assessed self-reported relationship satisfaction and narcissism. Results of multilevel models revealed that women with higher levels of narcissism demonstrated significantly higher levels of hostility, as did their male partners. Men also displayed more anger if their female partner had higher levels of narcissism. Narcissism was not associated with observed positive affect in any of the analyses. Results are consistent with previous research on couples in highlighting that women's narcissism is associated with more difficulties in romantic relationships for women and their male partners. Findings are discussed with attention to better understanding the behaviors that lead to dissatisfaction and dysfunction in romantic relationships where narcissism is present. Highlights: The relationship of narcissism to affect in a behavioral task between couples was investigated. When women's narcissism was higher, their own communication styles were more negative. When women's narcissism was higher, more negative communication was displayed by their partners. Narcissism was not related to displays of positive affect.